Design Development of Maternity Chair Backrests to Improve Comfort and Health (HEALTH CARE: JURNAL KESEHATAN, 2025)
Pregnancy with lower back pain is a common complaint that occurs in pregnant women. The back pain that is felt is closely related to the mother's position during pregnancy, especially sleeping position and body mechanics during pregnancy. The third trimester of pregnancy is the peak point for complaints of musculoskeletal pain, this is because the burden on the mother's stomach is getting heavier and the mother's spine and legs are trying hard to support her body. The aim of the research is to explore the discomfort, especially in the musculoskeletal system, experienced by pregnant 2women in the third trimester in the working area of the Rasau Kaya Community Health Center, Kubu Raya. The research method used was qualitative by conducting in-depth interviews with two pregnant women in the third trimester regarding musculoskeletal complaints or Musculoskeletal disorders they felt, which related to movement posture and discomfort experienced. The results of the research show that there are four major domains that can be addressed in this research, namely 1) the location and characteristics of the discomfort felt by pregnant women in the third trimester, 2) factors that cause discomfort, 3) how to overcome discomfort in the musculoskeletal system in pregnant women in the third trimester. . The conclusion from the research is that pregnant women in the third trimester experience very significant weight gain, so the body's burden will be the bones and muscles, so that some discomfort will arise in the bones and muscles, and there will be ways to reduce these complaints.